SET ESG ratings and firm value: The new sustainability performance assessment tool in Thailand - Mongkhol Moolkham (PLoS ONE, 2025)
This study investigates the influence of SET ESG ratings on firm value of companies listed on the Stock Exchange of Thailand (SET), emphasizing the multifaceted relationships between ESG performance, third-party evaluations, and market reactions following SET ESG ratings announcements. The findings reveal that firms with higher SET ESG ratings experience significant enhancements in firm value due to their superior management of environmental and social risks, which reduces regulatory and reputational threats. Furthermore, the research uncovers the nuanced role of third-party ESG evaluations, indicating that while endorsements from reputable sources can amplify the positive effects of SET ESG ratings, more or conflicting assessments can lead to diminished firm value. Specifically, a single strong endorsement markedly enhances firm value, whereas evaluations from two to three third parties may introduce confusion, leading to increased information asymmetry. This finding challenges the assumption that multiple endorsements always translate to greater value, emphasizing the need for firms to strategically select their evaluators to optimize market perceptions. Moreover, the study illustrates that announcements of SET ESG ratings result in immediate and sustained increases in firm value, highlighting ESG performance as a critical determinant of long-term viability in the eyes of investors. These results provide actionable guidance for investors and policymakers, advocating for the integration of robust ESG practices to enhance market confidence and drive long-term value creation. This research contributes to the existing literature by elucidating the intricate dynamics between SET ESG ratings, third-party evaluations, and firm value, thereby offering valuable perspectives for firms navigating a sustainability-focused landscape.